System under consideration is
Xn+1 is calculated depend on the xn values in each iteration
Code needs to do following steps:
Let initial value of xn=0;then
First iteration n=0:
As xn <0
Xn+1= axn+µ → x1=ax0+µ
Let this value >0 → x1 >0
Second Iteration n=1:
Xn+1=bxn+µ-1 → x2=bx1+µ-1 → x2=b(ax0+µ)+µ-1
Note: Need to store the x1,x2 variables in array .
Thanks for sharing.I found a lot of interesting information here. A really good post, very thankful and hopeful that you will write many more posts like this one.